Antigen-Specific Acquired Immunity in Human Brucellosis: Implications for Diagnosis, Prognosis, and Vaccine Development - Cannella, Anthony P.; Tsolis, Renee M.; Liang, Li; Felgner, Philip; Saito, Mayuko; Gotuzzo, Eduardo; Sette, Alessandro; Vinetz, Joseph M. (Frontiers in Cellular and Infection Microbiology, 2012)
Brucella spp., are Gram negative bacteria that cause disease by growing within monocyte/macrophage lineage cells. Clinical manifestations of brucellosis are immune mediated, not due to bacterial virulence factors. Acquired immunity to brucellosis has been studied through observations of naturally infected hosts (cattle, goats), mouse models (mice), and human infection. Even though Brucella spp. are known for producing mechanisms that evade the immune system, cell-mediated immune responses drive the clinical manifestations of human disease after exposure to Brucella species, as high antibody responses are not associated with protective immunity. The precise mechanisms by which cell-mediated immune responses confer protection or lead to disease manifestations remain undefined. Descriptive studies of immune responses in human brucellosis show that TH1 (interferon-γ-producing T cells) are associated with dominant immune responses, findings consistent with animal studies. Whether these T cell responses are protective, or determine the different clinical responses associated with brucellosis is unknown, especially with regard to undulant fever manifestations, relapsing disease, or are associated with responses to distinct sets of Brucella spp. antigens are unknown. Few data regarding T cell responses in terms of specific recognition of Brucella spp. protein antigens and peptidic epitopes, either by CD4+ or CD8+ T cells, have been identified in human brucellosis patients. Additionally because current attenuated Brucella vaccines used in animals cause human disease, there is a true need for a recombinant protein subunit vaccine for human brucellosis, as well as for improved diagnostics in terms of prognosis and identification of unusual forms of brucellosis. This review will focus on current understandings of antigen-specific immune responses induced Brucella peptidic epitopes that has promise for yielding new insights into vaccine and diagnostics development, and for understanding pathogenetic mechanisms of human brucellosis.